(untitled) (Politeja, 2023)
DEMOCRACY OF SWITZERLAND FROM THE PERSPECTIVE OF THE HERMENEUTICS OF MULTILINGUISTICALITY The aim of this article is to attempt to look at the phenomenon of the multilingual democracy of Switzerland, from the point of view of a methodological perspective called the hermeneutics of multilinguisticality, to answer the question of whether this proposal may prove useful in the area of a better understanding of the phenomena and processes taking place within that field. In a more detailed form, it considers the extent to which this relatively constant presence in the consciousness of the Swiss optic of multilingualism, can influence the ideas about potential solutions of a political and institutional sort.